Brazilian infant and preschool children feeding: literature review - Carolina Santos Mello; Karina Vieira Barros; Mauro Batista de Morais
Abstract Objective To assess the feeding profile of Brazilian infants and preschool children aged 6 months to 6 years, based on the qualitative and quantitative analysis of food and nutrient intake. Data source This review analyzed studies carried out in Brazil that had food survey data on infants and preschool children. The search was limited to publications from the last 10 years included in the LILACS and MEDLINE electronic databases. Data summary The initial search identified 1480 articles, of which 1411 were excluded after the analysis of abstracts, as they were repeated or did not meet the inclusion criteria. Of the 69 articles assessed in full, 31 articles contained data on food survey and were selected. Only three studies concurrently assessed children from different Brazilian geographical regions. Of the assessed articles, eight had qualitative data, with descriptive analysis of food consumption frequency, and 23 had predominantly quantitative data, with information on energy and nutrient consumption. Conclusions The articles assessed in this review showed very heterogeneous results, making it difficult to compare findings. Overall, the feeding of infants and preschool children is characterized by low consumption of meat, fruits, and vegetables; high consumption of cow's milk and inadequate preparation of bottles; as well as early and high intake of fried foods, candies/sweets, soft drinks, and salt. These results provide aid for the development of strategies that aim to achieve better quality feeding of Brazilian infants and preschoolers.